SENI DOLALAK PURWOREJO JAWA TENGAH: PERAN PEREMPUAN DAN PENGARUH ISLAM DALAM SENI PERTUNJUKAN - Santosa, Djarot Heru (Jurnal Kawistara, 2013)
The role of women artists in the performing arts, also within the arts as well as the other broader life, inIndonesia, seems to be strengthening in recent years. It doesnât mean that it is a new issue, of course. Butperhaps it happened since Indonesia experiencing and witnessing a great change of mainstream withinit self since 1998; this issue, as well as the other critical issues gaining a more free momentum and spaceof expression. Of course, this still needs further scrutinization. The superiority of women is not limitedto the mith in which giving special space for them, but indeed women have strong key role as the escortof performing arts. Women have the central key in promoting traditional arts; however, there is womenrole shift in the stage of performing arts. Women artists in the culture posseses inevitable duality ofposition. They are praised as high as the sky, in the other hand they are also insulted, abused, and usedas a profit-making commodity. Besides their beautiful manner and behaviour, women are also capableof breaking through the boundary of culture. Women as the mother earth whoâs also identical withthe symbol of fertility, paragon, and the parameter of values and norms that is expected by the socialcommunity, are also capable of fulfilling the promises attached into the miths that praise and adorethem. Therefore, it is their nature that they have the central role in the success of a performing art bothtraditional and modern. Serious problems in the world of performing arts occur when women artists tryto promote tradition. Inner conflict uccur between their basic nature and their environemntal condition.In this case, pressures are not only coming from the social environment but also from within. In fact,the soul of tradition survives and sustain from their very hands. When the stage experiences shift, therole of women as the escort of the tradition is also fading. Performance industry does properly placestage women as a subject but only as a commodity to attarct the market for the capitalists. Together, weshould be able to solve this problem if we still want women to attend in the world of performing artsand change the world into a more colorful one.